Planning and development of an antimicrobial stewardship program in penitentiary facilities: strategies to optimize therapeutic prescribing and reduce the incidence of antibiotic resistance - Mazzoleni, Ludovica; Zovi, Andrea; D'Angelo, Cinzia; Borsino, Cecilia; Cocco, Nicola; Lombardo, Raffella Carla; Ranieri, Roberto (Frontiers in Public Health, 2023)
Introduction In correctional facilities, due to the high incidence of bacterial infections, antibiotics are widely prescribed. As a result, it may occur a massive and improper use of antibiotics, which promotes the development of antibiotic-resistant bacteria. However, in literature, specific experiences, interventions or guidelines aimed to optimize their prescription within prisons are sporadic. Objectives In an Italian hospital where belong patients from four penitentiary institutions, a multidisciplinary team has implemented an antimicrobial stewardship project. The aim of the project was to reduce the incidence of antibiotic resistance in penitentiary institutions by optimizing and rationalizing antibiotic prescribing. Methods Following the analysis of microbiological prevalence and antibiotic consumption data within correctional facilities, the Antimicrobial Stewardship Team developed operational tools to support prison healthcare staff to manage properly antibiotic therapies. Results The analysis showed a gradual increase in antibiotic resistance: in 2021 the prevalence of resistant microorganisms was 1.75%, four times higher than in 2019. In contrast, between 2019 and 2021, antibiotic consumption decreased by 24%. Based on consumption data, pharmacy has drafted an antibiotic formulary for correctional facilities, supplemented with guidelines and data sheets, and also developed a prescription form for critical antibiotics. Conclusion Results showed an increasing incidence of antibiotic resistance within prisons, highlighting the need to establish a dedicated antimicrobial stewardship program. This project may impact positively not only on prisoners, but also for the entire community, as prisons can be considered as places of health education and promotion.